Catalytic Intramolecular C(sp3)–H Amination of Carbamimidates. Issue 14 (11th April 2017) - Grelier, Gwendal; Rey‐Rodriguez, Romain; Darses, Benjamin; Retailleau, Pascal; Dauban, Philippe
Abstract : The Rh II ‐catalyzed intramolecular C(sp 3 )–H amination of carbamimidates allowed new nitrogen heterocycles to be isolated in yields up to 99 %. The reaction was best performed in the presence of the Rh2 (esp)2 (esp = α, α, α′, α′‐tetramethyl‐1, 3‐benzenedipropionic acid) complex by using 2, 2, 2‐trichloroethoxysulfonyl‐protected compounds. The reaction could be applied to substrates possessing a benzylic, an allylic, a propargylic, or a tertiary C(sp 3 )–H bond. Abstract : The Rh II ‐catalyzed intramolecular C(sp 3 )–H amination of carbamimidates allows new nitrogen heterocycles to be isolated in yields up to 99 %. The reaction can be applied to benzylic, allylic, and propargylic substrates as well as to derivatives containing tertiary sites. esp = α, α, α′, α′‐tetramethyl‐1, 3‐benzenedipropionic acid; Tces = 2, 2, 2‐trichloroethoxysulfonyl.